Circadian disruption of memory consolidation in Drosophila - Yin, Jerry C. P.; Cui, Ethan; Hardin, Paul E.; Zhou, Hong (Frontiers in Systems Neuroscience, 2023)
The role of the circadian system in memory consolidation is an important question in neurobiology. Despite this hypothesis being intuitively appealing, the existing data is confusing. Recent work in Drosophila has helped to clarify certain aspects of the problem, but the emerging sense is that the likely mechanisms are more complex than originally conceptualized. In this report, we identify a post-training window of time (during consolidation) when the circadian clock and its components are involved in memory consolidation. We use post-training environmental and inducible transgenes, as well as a chronic mutant to establish this relationship. Our analysis suggests that disruptions to sleep are not likely to contribute to the memory problems. Although there are small effects on circadian locomotor activity, our manipulations do not affect the overall architecture of activity. We suggest that our manipulations are affecting another aspect of memory consolidation. In the broader context our data suggests that circadian biology might have multiple roles during consolidation. Testing for its roles at multiple timepoints, and in different cells, will be necessary to resolve some of the conflicting data.